Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.intimp.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

A journey with Tony Hugli up the inflammatory cascade towards the auto-digestion hypothesis

Abstract: My association with Tony Hugli, long-term editor of Immunopharmacology and International Immunopharmacology, came about by a specific and long-standing problem in inflammation research. What is the trigger mechanism of inflammation in physiological shock? This is an important clinical problem due to the high mortality associated with physiological shock. We joined forces in the search of the answer to this question for more than a decade. Our journey eventually led to development of the hypothesis that shock m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…These enzymes are normally contained in the lumen of the intestine where they work by breaking down a broad spectrum of biological molecules into their building blocks suitable for transport across the mucosal epithelium and subsequently into the circulation. It has been shown that in situations of ischemia and reperfusion of the gut these powerful digestive enzymes play a central role in the destruction of the intestines and other tissues if they can no longer be compartmentalized within the intestinal lumen [5][6][7]. Under conditions where the mucosal barrier is compromised, the fully activated proteolytic enzymes initiate an auto-digestion process, initially in the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes are normally contained in the lumen of the intestine where they work by breaking down a broad spectrum of biological molecules into their building blocks suitable for transport across the mucosal epithelium and subsequently into the circulation. It has been shown that in situations of ischemia and reperfusion of the gut these powerful digestive enzymes play a central role in the destruction of the intestines and other tissues if they can no longer be compartmentalized within the intestinal lumen [5][6][7]. Under conditions where the mucosal barrier is compromised, the fully activated proteolytic enzymes initiate an auto-digestion process, initially in the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic enzymes in the pancreatic fluid (PF) may play a central role in the destruction of various tissues because of their ability to cause proteolytic and lipolytic cleavage of the extracellular domain of membrane receptors, resulting in the loss of associated cellular functions. The enzymes may also trigger mechanisms for tissue inflammation and could be the instigating event for the release of a host of strong inflammatory mediators [5][6][7]. PF is released in particularly large amounts from the pancreas after acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Our initial hypothesis followed traditional thinking that there is a mediator in the plasma (e.g. endotoxins, complement components, reactive oxygen species, lipid mediators) that may be responsible for the activation [ 39 ]. Some of these mediators may not only serve to activate but may also be cytotoxic by themselves or as a mixture of different mediators [ 40 , 41 ].…”
Section: Mechanisms Leading To Leukocyte Activationmentioning
confidence: 99%
“…The specific mechanism(s) by which plasma may produce cell activation remained uncertain. After years of attempts to identify the inflammatory mediators with classical biochemical approaches [ 39 ] we recognized the need for a new approach to this fundamental problem in the pathogenesis of hemorrhagic shock.…”
Section: Mechanisms Leading To Leukocyte Activationmentioning
confidence: 99%
“…The permeability increases and, as a result, intestinal contents may leak across the mucosal barrier [7] , [8] . After escape from the intestinal lumen, intestinal contents can be transported through the venous intestinal vasculature [9] , [10] , lymphatics [11] , [12] , or via the peritoneum into the systemic circulation [13] , [14] , and may be responsible for distant organ injury [12] , [15] . While many studies have investigated the transport of material into the blood and lymphatics from the intestine, few have investigated the importance of the transmural permeability in mammalian species, a route that provides direct access to peripheral organs, despite its association with poor outcome and death [11] , [14] , [16] .…”
Section: Introductionmentioning
confidence: 99%